The effect of Cd (II), Pb (II) and Cu (II) ions on the growth and bioaccumulation properties of Rhizopus arrhizus - Uslu, G; Dursun, AY; Ekiz, HI; Aksu, Z (Elsevier Sci Ltd, 2003)
The comparative growth and Cd (11), Pb (11) and Cu (11) ions bioaccumulation properties of Rhizopus arrhizus were investigated as a function of initial pH, temperature and initial metal ion concentrations. The optimum initial pH for Cd (11), Pb (11) and Cu (11) were determined as 3.5, 4.0 and 4.5 at optimum temperatures for each metal ion, respectively. Results indicated that microbial growth and metal ion uptake of R. arrhizus were significantly affected by initial metal ion concentrations. High microbial growth and Cd (11), Pb (11) and Cu (11) accumulation yields were found at low initial metal ion concentrations. R. arrhizus was more efficient in accumulating larger amounts of Cd (11) and Ph (11) ions than that of Cu (11) ions. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: bioaccumulation; Cd (II); Pb (II); Cu (II); viable R. arrhizus